Baptismal Well at Our Lady of the Rosary Church - Mumbai Archive Project Team (Jio Institute, 2024)
The baptismal well at Our Lady of the Rosary is dedicated to Joseph Baptista, who was born in Matharpacady on January 4, 1864. Baptista was a fervent nationalist who studied law to become a barrister. As a member of the Indian National Congress (INC), he significantly contributed to the mobilization of public opinion in support of Indian Home Rule through his writings, speeches, and political engagement.